The Effect Of Perceived Organizational Support, Organizational Justice On Employee Performance With Job Satisfaction As A Mediation Variable At PT Sampoerna Kayoe Bukateja - Muhammad Ihza Alfania; Alfato Yusnar Kharismasyah; Fatmah Bagis; Luthfi Zamakhsyari (Cita konsultindo, 2025)
This study aims to examine the effect of Perceived Organizational Support, organizational justice on employee performance with job satisfaction as a mediating variable. The population in this study were employees of PT. Sampoerna Kayoe Bukateja engaged in the production of processed wood in Purbalingga. This study applies a quantitative approach method. The sample used was 185 employees and respondents were obtained using non-probability sampling with purposive sampling. The type of data in this study is primary data and the instrument used in data collection is a questionnaire with a 5-point Likert scale measurement. While the analysis technique used is SEMPLS version 3.0. The results of the study indicate that Perceived Organizational Support and organizational justice have a positive and significant effect on job satisfaction, Perceived Organizational Support and organizational justice have a positive and significant effect on employee performance, Perceived Organizational Support and organizational justice have a positive and significant effect on satisfaction, satisfaction mediates the effect of organizational justice on employee performance, and satisfaction mediates the effect of Perceived Organizational Support on employee performance.